2021
DOI: 10.1183/23120541.00983-2020
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in COPD: a systematic review and meta-analysis of studies using different functional assessment methods

Abstract: BackgroundCardiovascular disease is a major cause of morbidity and mortality in chronic obstructive pulmonary disease (COPD). Endothelial dysfunction is suggested to be one of the pathogenetic mechanisms involved. This is a systematic review and meta-analysis of studies using any available functional method to examine differences in endothelial function between patients with COPD and individuals without COPD (controls).MethodsLiterature search involved PubMed and Scopus databases. Eligible studies included adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…Therefore, CDC42 expression may be increased in patients with COPD due to an as yet unknown compensatory mechanism. In addition, patients with AE-COPD typically experienced longer disease durations compared with those in patients with stable COPD, such that prolonged disease may enhance endothelial dysfunction and disease severity ( 24 ). Since CDC42 has been demonstrated to exert a protective effect against endothelial injury, CDC42 expression was higher in patients with AE-COPD compared with that in patients with S-COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CDC42 expression may be increased in patients with COPD due to an as yet unknown compensatory mechanism. In addition, patients with AE-COPD typically experienced longer disease durations compared with those in patients with stable COPD, such that prolonged disease may enhance endothelial dysfunction and disease severity ( 24 ). Since CDC42 has been demonstrated to exert a protective effect against endothelial injury, CDC42 expression was higher in patients with AE-COPD compared with that in patients with S-COPD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that NO-mediated endothelial relaxation in COPD patients is present early in the disease and is associated with airflow obstruction (61). The results of multiple meta-analyses have also confirmed that COPD endothelial function is impaired, and the severity is positively correlated with the degree of airway obstruction (62)(63)(64). Endothelial dysfunction in COPD may be involved in the following aspects ( 65 (5) Antioxidant Pathway activation decreased; (6) NO release decreased, endothelin-1 expression increased and so on.…”
Section: Vascular Endothelial Dysfunctionmentioning
confidence: 94%
“…Дисбаланс между вазодилататорами и вазоконстрикторами (увеличение ЭТ-1, снижение концентрации NO в крови), изменения сосудистого русла непосредственно в бронхиальной стенке вносят значимый вклад в формирование необратимой бронхиальной обструкции и хронической легочной гипертензии [23][24][25].…”
Section: Introductionunclassified